Cell-free biology using remote-controlled digital microfluidics for individual droplet control. Issue 45 (20th July 2020) - Liu, Dong; Yang, Zhenghuan; Zhang, Luyang; Wei, Minglun; Lu, Yuan
Abstract : Cell-free biology using remote-controlled digital microfluidics for programmed biological screening and synthesis. Abstract : Cell-free biology for diverse protein expression and biodetection in vitro has developed rapidly in recent years because of its more open and controllable reaction environment. However, complex liquid handling schemes are troublesome, especially when scaling up to perform multiple different reactions simultaneously. Digital microfluidic (DMF) technology can operate a single droplet by controlling its movement, mixing, separation, and some other actions, and is a suitable scaffold for cell-free reactions with higher efficiency. In this paper, a commercial DMF board, OpenDrop, was used, and DMF technology via remote real-time control inspired by the Internet of Things (IoT) was developed for detecting glucose enzyme catalytic cell-free reactions and verifying the feasibility of programmed cell-free protein expression. A cell-free biological reaction process which can be remote-controlled visually with excellent interactivity, controllability and flexibility was achieved. As proof-of-concept research, this work proposed a new control interface for single-drop cell-free biological reactions. It is much like the "droplet operation desktop" concept, used for remote-controllable operations and distributions of cell-free biology for efficient biological screening and protein synthesis in complex reaction networks, with expanded operability and less artificial interference.